The five senses in medieval and early modern England - Kern-Stähler, Annette, 1971-; Busse, Beatrix; Boer, Wietse de (Intersections (Boston, Mass.) ;, 2016)
These essays offer a fresh perspective on the interrelationships between sense perception and secular and Christian cultures in England from the Middle Ages into the Early Modern period.